Rewrite the following equation so that y is a function of x:3x + 18y = 36 Show how you got the answer.....
Okay so obviously you have to solve the equation for y, to get f(x). So by doing that just distribute "3x" to the other side of the equation. Then divide it all by 18. And Ill leave it there to let you figure the rest out. ;)
i'm not in collage sooo...
im just in middle school
try getting Y by itself
3X=-18y of course
3x + 18y = 36To make y a function of x, solve for y. 3x + 18y = 36-3x. -3x18y = -3x + 36/18. /18y = -3x/18 + 36/18y = (-1/6)x + 2. ANSWER